Smart Learning in a Smart Era: The Use of Digital Literacy, Artificial Intelligence (AI), and Learning Styles as Predictors of Students’ Learning Outcomes - Andy Prasetyo Wati; Rachmad Hidayat; Jefry Aulia Martha; Aryati Binti Abd Rahman (Global Educational Research Review, 2025)
Purpose – The focus or main purpose of this study emphasizes appropriate collaboration between the roles of digital literacy, AI platforms, and learning styles in learners so that it provides a significant impact on learning effectiveness, particularly on learners' learning outcomes. Methods/Design/Approach – This study uses a quantitative approach, with a multiple linear regression method. The population and sample are students of Vocational High School (SMK) in East Java, with a research sample of 384 respondents using random sampling and Cochran calculation. Data collection uses a questionnaire (survey) method with a 7-point Likert scale. Validity and reliability tests are used to test the feasibility of the instrument, and continued with model feasibility testing using the classical assumption test, while hypothesis testing uses multiple linear regression test analysis. Findings – The results show that partially and simultaneously the variables of digital literacy, artificial inttelegence, and learning styles have a significant effect on learning outcomes. This is seen from the t-count value > t-table [DL: 6.020 > 1.966; AI: 4.408 > 1.966; 14.166 > 1.966], and also the F-count value > F-table [250.106 > 2.268], in addition the R-Square value also shows 0.664. Originality/Value – This study has strong originality because it simultaneously examines the roles of digital literacy, the use of artificial intelligence (AI)-based platforms, and learners' learning styles in influencing learning effectiveness. This study has not been widely conducted comprehensively, thus providing a new contribution in understanding how these three aspects interact with each other and impact the quality of the teaching and learning process in the digital era. Practical Implications – These findings emphasize more on how all actors in education (students, teachers, and educational institutions) are able to integrate digital literacy into the curriculum, utilize artificial intelligence (AI)-based learning platforms that support personalization, and map students' learning styles early to adjust teaching strategies. Keywords AI, learning effectiveness, learning styles, learning outcomes, digital literacy Paper type Research paper